Jejak Sejarah Sosial Pendidikan Islam Anak di Indonesia: Kajian Nilai Edukatif Antar Zaman - Zulkifli, Zulkifli; Samad, Duski; Sutan Mamad, Firdaus; Kurnia, Asraf (LP2M STAI Darul Kamal NW Kembang Kerang, 2025)
This study aims to identify the transformation of Islamic educational thought for children in Indonesia and the accompanying educational values throughout history. Using a descriptive qualitative approach with content and historical analysis, data were collected from classical and contemporary literature, educational documents, and the works of Islamic education figures. The findings reveal that Islamic education for children is dynamic and context-sensitive. In the pre-colonial period, it emphasized morality and spirituality rooted in community-based learning. During the colonial era, Islamic and national values were integrated. The post-independence era marked the formalization of education with a focus on character and social responsibility. In the contemporary era, the approach highlights inclusiveness, digital literacy, and religious moderation. The study concludes that Islamic child education remains rooted in Islamic core values while adapting to socio-cultural dynamics.